SEBARAN UNSUR DAN ASOSIASI UNSUR Fe LATERIT BESI DAERAH BLOK X, PT SILO, PULAU SEBUKU, KALIMANTAN SELATAN: ELEMENTAL DISTRIBUTION ANALYSIS AND ELEMENTAL ASSOCIATION OF Fe LATERITC IRON, BLOCK X AREA, PT SILO, SEBUKU ISLAND, SOUTH KALIMANTAN - Andri B Situmorang; Suprapto, Sabtanto Joko; W, A. Djumarma; Widhiyatna, Denni; Mutia, Sarah; Cahyadi, Andhi (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2024)
The study area is located in Blok X, PT SILO, Sebuku Island, South Kalimantan. The geology of the study area is dominated by serpentinized ultramafic rocks, which have a high potential for the formation of lateritic iron minerals. The aim of the investigation of the area was to determine the vertical and horizontal distribution of the element contents and the association of the iron elements. Drilling, sample analyses using XRF, petrography and statistical analyses of correlation matrices and dendrograms were carried out. Fe, Ni, P, Co, Si, Mg, Cr, Al, Mn, Ca, Na, K and Ti were analyzed in 5.150 samples using the XRF method. The high iron content is found in the red limonite zone with 40-55% and in the yellow limonite zone with 40-52%. The lithology of the area with high iron content is ophiolitic ultramafic rock. In the vertical distribution profile, the high iron content is also found in the red limonite - yellow limonite zone. Based on the dendrogram analysis and the correlation matrix, the correlation of the Fe elements in the study area shows that the Fe elements are strongly correlated with the Co, Cr and Mn elements and generally with the Ni elements. Elemental iron is strongly negatively correlated with the elements Si and Mg.